Transformation of Graphs Andrew Robertson
Transformation of f(x)+a f(x) = x2
Transformation of f(x)+a y = x2 + 3
Transformation of f(x)+s y = x2 - 2
Transformation of sf(x) f(x) = (x-2)(x-3)(x+1) 2f(x)
Transformation of sf(x) y=2f(x) = 2(x-2)(x-3)(x+1) 0.5f(x)
Transformation of sf(x) y=0.5f(x) = 0.5(x-2)(x-3)(x+1)
Transformation of f(x+s) f(x) = x2 f(x-2)
Transformation of f(x+s) y=f(x-2) = (x-2)2 f(x+2)
Transformation of f(x+s) y=f(x+2) = (x+2)2
Transformation of f(sx) f(x) = (x-2)(x-3)(x+1) f(2x)
Transformation of f(sx) y=f(2x) = (2x-2)(2x-3)(2x+1) f(0.5x)
Transformation of f(sx) y=f(0.5x) = (0.5x-2)(0.5x-3)(0.5x+1) -f(x)
Transformation of -f(x) f(x) = (x-2)(x-3)(x+1) -f(x)
Transformation of -f(x) y=-f(x) = -[(x-2)(x-3)(x+1)] f(-x)
Transformation of f(-x) f(x)=(x-2)(x-3)(x+1) y=f(-x)=(-x-2)(-x-3)(-x+1)
Combinations of transformations f(x)= x2 then y=f(x+2)-3 = (x+2)2 -3
Combinations of transformations y = x2 then y=-2f(x-3) = -2(x-3)2
F(αx±β) - Inside brackets always effects the horizontal αF(x) ±β - Outside brackets always effects the vertical
f(x) ± a Vertical shift (x,y) -> (x, y ± a) f(x ± a) Horizontal shift (x,y) -> (x a, y) Note that when + shift to Left and – shift to Right αf(x) Vertical Stretch/compression by factor α (x,y) -> (x, αy) f(αx) Horizontal Stretch/compression by factor 1/α (x,y) -> (x/α, y) f(-x) Refection though y axes (x,y) (-x, y) - f( x) Reflection through x axes (x,y) ( x, -y)